PENGARUH KARAKTERISTIK PEKERJAAN DAN KOMPENSASI FINANSIAL TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN - Narottama, I Gde Hendra; Surya, Ida Bagus Ketut (E-Jurnal Manajemen, 2015)
The aim of this study is 1) to analyze the direct effect of job characteristics and financial compensation to job satisfaction, 2) to analyze the indirect influence of job characteristics and financial compensation to employee performance through job satisfaction, and 3) to analyze the direct influence of job satisfaction on employee performance. This research was conducted at KPN. Kamadhuk RSUP. Sanglah located in Denpasar - Bali. Respondents in this study were all employees amounted to 77 people. Data collected by questionnaires that use 5-point Likert scale to measure 19 indicators. Data analysis technique used is path analysis (path analysis). The research proves that there is directly positive and significant job characteristics and financial compensation toward job satisfaction, there is the indirect effect of job characteristics and financial compensation to employee performance through job satisfaction and there is an influence job satisfaction on employee performance.
Keywords: job characteristic, ,financial compensation, job satisfaction, employee performance